2014
DOI: 10.1111/exd.12529
|View full text |Cite
|
Sign up to set email alerts
|

Serum Th1/Th2 and macrophage lineage cytokines in leprosy; correlation with circulating CD4+CD25highFoxP3+ T‐regs cells

Abstract: Not only macrophages, T-helper (Th)1 and Th2, but also CD4(+) CD25(high) FoxP3(+) regulatory T cells (T-regs) are involved in immune response to Mycobacterium leprae. We aimed to evaluate serum interleukin (IL)-1β and IL-12p70 (macrophage cytokines), interferon-γ (IFN-γ) (Th1 cytokine), IL-4 (Th2 cytokine) and circulating CD4(+) CD25(high) FoxP3(+) T-regs, in untreated leprosy patients. Forty three patients and 40 controls were assessed for the mentioned cytokines using ELISA. Patients were assessed for circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
2
8
0
Order By: Relevance
“…Comparing to other forms of leprosy and healthy controls, T2R showed lowest circulating Treg frequency, which was consistent with the high Th17 frequency in T2R (58,76). But it is not the case for T1R, several studies have demonstrated that T1R showed a significantly higher frequency of Treg compared to nonreactional leprosy in both PBMC and skin lesions (58,74,(76)(77)(78). One possible explanation for the increase of Treg in T1R is that the increase of Treg in T1R is a self-protection mechanism to reduce the tissue damage caused by the exacerbated cell-mediated immune responses.…”
Section: The Reciprocal Relationship Between Regulatory T Cells and Tsupporting
confidence: 79%
See 2 more Smart Citations
“…Comparing to other forms of leprosy and healthy controls, T2R showed lowest circulating Treg frequency, which was consistent with the high Th17 frequency in T2R (58,76). But it is not the case for T1R, several studies have demonstrated that T1R showed a significantly higher frequency of Treg compared to nonreactional leprosy in both PBMC and skin lesions (58,74,(76)(77)(78). One possible explanation for the increase of Treg in T1R is that the increase of Treg in T1R is a self-protection mechanism to reduce the tissue damage caused by the exacerbated cell-mediated immune responses.…”
Section: The Reciprocal Relationship Between Regulatory T Cells and Tsupporting
confidence: 79%
“…Since T1R and T2R are both acute inflammation reactions, it is reasonable to discover a higher frequency of Th17 in both T1R and T2R compared to non-reactional leprosy considering the inflammation functions of Th17 cells (73)(74)(75). Comparing to other forms of leprosy and healthy controls, T2R showed lowest circulating Treg frequency, which was consistent with the high Th17 frequency in T2R (58,76). But it is not the case for T1R, several studies have demonstrated that T1R showed a significantly higher frequency of Treg compared to nonreactional leprosy in both PBMC and skin lesions (58,74,(76)(77)(78).…”
Section: The Reciprocal Relationship Between Regulatory T Cells and Tsupporting
confidence: 65%
See 1 more Smart Citation
“…These findings may be of great relevance since keratinocytes play a key role in the initiation of primary immune responses in the skin (19). Furthermore, Abdallah M. et al (60) showed higher serum IL1β levels in multibacillary leprosy patients when compared to paucibacillary patients, suggesting a proinflammatory role for IL1β in multibacillar leprosy. TNFα and IL1β are important cytokines inducing the emigration of Langerhans cells (LC) from lymphoid tissues (61).…”
Section: Accepted Articlementioning
confidence: 93%
“…Therefore, the observation of lower numbers of Tregs in ENL could account for the relatively higher proportion of T cells previously described in multiple ENL studies. Two more publications from the same group addressed the frequency of Tregs in ENL, defined as CD4 + CD25 high FoxP3 + cells and reported the ratio of Treg/Teffector cells to be low in ENL (109, 110). These results should be interpreted with caution since dichotomizing cells into CD25 high and CD25 low to identify Tregs is highly subjective.…”
Section: What Is the Role Of T-cells In Enl?mentioning
confidence: 99%